The Technique Analysis of CO2 in Troposphere using AIRS - Ningsih, Nunung Isnaini Dwi (Proceeding International Conference on Science and Engineering, 2017)
Currently global warming has become an international issue. One of the biggest contributors to global warming is carbon dioxide (CO2). CO2 gas is one of the most prominent gases of greenhouse gases or greenhouse gases in the atmosphere and has an important role in the Earth's climate. Increased CO2 contributes more than 50% to the effects of global warming. Various methods and measuring instruments of CO2 concentration developed from optical sensors to measuring CO2 directly from space using satellites. Atmosphere Infrared Sounder (AIRS) is one of NASA's six (6) instances launched on May 4, 2002 installed on the AQUA satellite. This instrument uses sounding technology that determines the vertical profile of CO2 from space. This instrument supports climate-related research and also in improving weather forecasts. AIRS data can be obtained online from the Giovanni Website at http://giovanni.gsfc.nasa.gov. Giovani is an application provided by NASA to make it easier to acquire, visualize, and analyze remote sensing data with ASCII data facilities that can be downloaded directly. The purpose of this research is to conduct CO2 analysis in Indonesia online using Giovanni Website year 2013-2016. Rendering data online shows the CO2 fluctuated every month, but yearly data shows the CO2 increased signifantly and the higest value in 2016, its reach 4.039 ppm. The results of CO2 analysis is expected to assist in the process of prevention or reduction of CO2 emissions in the air as one of the activities of environmental conservation.